1986
DOI: 10.1128/jcm.23.5.891-896.1986
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Yersinia intermedia-like bacteria isolated from patients with diarrhea in Nigeria

Abstract: Five Yersinia strains, biochemically mimicking Yersinia intermedia, were isolated from patients with acute diarrheal diseases seen at the University of Lagos (Nigeria) Teaching Hospital between October 1979 and September 1982. The five isolates utilized citrate as their source of carbon and fermented sucrose, L-rhamnose, and a-methyl-D-glucoside, but unlike any other Y. intermedia biogroup, they failed to ferment D-melibiose or D-raffinose. They all belonged to serogroup 0:52,53. Four autoagglutinated and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As iron-overloaded mice succumbed within 24 h of intraperitoneal inoculation, the authors suggested that mouse pathogenicity of Y. kristensenii, especially O serogroups O:11, O:12,25, and O:16, may be attributed to a mechanism not previously recognized in yersiniae. Perhaps the same is true for Y. intermedialike isolates and Y. frederiksenii (4,10,29,183) recovered from diarrheagenic stools.…”
Section: Assessment For Virulence Traitsmentioning
confidence: 88%
“…As iron-overloaded mice succumbed within 24 h of intraperitoneal inoculation, the authors suggested that mouse pathogenicity of Y. kristensenii, especially O serogroups O:11, O:12,25, and O:16, may be attributed to a mechanism not previously recognized in yersiniae. Perhaps the same is true for Y. intermedialike isolates and Y. frederiksenii (4,10,29,183) recovered from diarrheagenic stools.…”
Section: Assessment For Virulence Traitsmentioning
confidence: 88%
“…Strains of all Y. enterocolitica ‐like species have been isolated from clinical specimens [4,5], and virulence factors have been detected in several strains of these species [6–12]. In addition, certain strains of Y. enterocolitica ‐like species have been shown to cause human disease [4,13,14]. Recently, Loftus et al showed that up to 20% of all yersiniae isolated from stool specimens of patients with gastrointestinal symptoms may represent Y. enterocolitica ‐like strains [15].…”
Section: Introductionmentioning
confidence: 99%
“…According to Robins-Browne (2001), Y. intermedia species are not related to human disease but are commonly obtained from terrestrial and freshwater. However, there is growing epidemiological and experimental evidence to suggest that some Y. intermedia isolated from human can cause disease (Agbonlahor, 1986). These authors suggest that there may be two subgroups of Y. intermedia: pathogenic strains of clinical origin and nonpathogenic strains that occur in the environment.…”
Section: Discussionmentioning
confidence: 99%